Modeling of bubble‐size distribution in water and freon co‐blown free rise polyurethane foams. Issue 18 (14th April 2014) - Niyogi, Debdarsan; Kumar, Rajinder; Gandhi, Kandukuri S.
ABSTRACT A model has been developed to simulate the foam characteristics obtained, when chemical (water) and physical (Freon) blowing agents are used together for the formation of polyurethane foams. The model considers the rate of reaction, the consequent rise in temperature of the reaction mixture, nucleation of bubbles, and mass transfer of CO2 and Freon to them till the time of gelation. The model is able to explain the experimental results available in literature. It further predicts that the nucleation period gets reduced with increase in water (at constant Freon content), whereas with increase in Freon (at constant water) concentration nucleation period decreases marginally leading to narrower bubble‐size distribution. By the use of uniform sized nuclei added initially, the model predicts that the bubble‐size distribution can be made independent of the rate of homogeneous nucleation and can, thus, offer an extra parameter for its control. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40745.